2016
DOI: 10.18203/2320-6012.ijrms20162896
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nutritional deficiencies other than anaemia among students of government commerce college of Gandhinagar, Gujarat: a cross sectional study

Abstract: INTRODUCTIONAdolescence and young adulthood are periods of critical development and transition. These young people undergo major physical, cognitive, and psychosocial changes. These changes have important implications for health. As young people become increasingly independent, they face significant choices in areas such as diet, substance use, sexuality, physical activity and use of health care services. These choices are shaped by individual, family, social environments, and other contextual factors. A colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…The prevalence of nightmare at 6% in this current study is comparable to the prevalence of 3% and 4.7% in India and China respectively. 17,41 Meanwhile, Schlarb et al in their study suggested that nightmare predicted insomnia very well contrary to the observation in our current study. 42 This is important as dream recalling has been previously reported to be the hallmark of REM sleep.…”
Section: Pattern Of Sleepcontrasting
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nightmare at 6% in this current study is comparable to the prevalence of 3% and 4.7% in India and China respectively. 17,41 Meanwhile, Schlarb et al in their study suggested that nightmare predicted insomnia very well contrary to the observation in our current study. 42 This is important as dream recalling has been previously reported to be the hallmark of REM sleep.…”
Section: Pattern Of Sleepcontrasting
confidence: 99%
“…Unlike the previously reported low prevalence of poor sleep of 7.7%, 9.9% and 10.6% among university students in Germany, Lebanon and Nigeria respectively the observed prevalence of clinical insomnia is more than twice higher in this current study at 24%, which is nearly the same at 25% and 26% reported in India and Jordan respectively, but lower than the 40.7% in Athens. 5,8,[15][16][17][18] This current finding and previous studies aligned with the empirical evidence suggesting that poor sleep quality is preponderant among medical students globally. 19 However, our result did not find any gender-related association with insomnia, consistent with other previous finding, but contrary to other work that demonstrated such association.…”
Section: Prevalence Of Insomnia Among Medical Studentssupporting
confidence: 91%
“…Individual, family, social environment and other contextual factors shape these choices. 1 be barriers to attending school and to learning. Schools provide an environment, for learning skills, and for development of intelligence that can be utilized by students to achieve their goals in life.…”
Section: Introductionmentioning
confidence: 99%